Associations of the Polymorphisms in ADIPOQ with Circulating Levels of Adiponectin and Lipids: A Meta-Analysis - Su, Mi; Jia, Aimei; He, Yilan; Song, Yongyan (Hormone and Metabolic Research, 2021)
The relationships between the rs266729, rs1501299, and rs2241766 polymorphisms in adiponectin gene (ADIPOQ) and circulating levels of adiponectin and lipids remain to be clarified. Databases including PubMed and Embase were searched for eligible studies. The random-effects model was used, and standardized mean difference (SMD) with 95% confidence interval (CI) was calculated to estimate the differences in circulating levels of adiponectin and lipids between the subjects with different genotypes. A total of 12 810, 17 319, and 21 361 subjects were identified in the analyses for the rs266729, rs1501299, and rs2241766 polymorphisms, respectively. G allele carriers of the rs266729 polymorphism had lower levels of adiponectin (SMD=–0.28, 95% CI=–0.43 to–0.12) and high-density lipoprotein cholesterol (HDL-C) (SMD=–0.10, 95% CI=–0.17 to–0.02) than CC homozygotes; T allele carriers of the rs1501299 polymorphism had higher levels of adiponectin (SMD=0.21, 95% CI=0.05 to 0.36) and HDL-C (SMD=0.09, 95% CI=0.04 to 0.15) and lower levels of triglycerides (SMD=–0.06, 95% CI=–0.12 to–0.01) than GG homozygotes; G allele carriers of the rs2241766 polymorphism had lower levels of adiponectin (SMD=–0.18, 95% CI=–0.31 to–0.05) and HDL-C (SMD=–0.12, 95% CI=–0.20 to–0.04) than TT homozygotes. This meta-analysis suggests that the rs266729, rs1501299, and rs2241766 polymorphisms of ADIPOQ are significantly associated with circulating levels of adiponectin and lipids, which may partly explain the associations between these polymorphisms and coronary artery disease.
Keywords: coronary artery disease; adiponectin; lipid; polymorphism